Representasi Konsep Diri Cantik Dalam Video Klip (Analisis Semiotika Video Klip Beyonce - Pretty Hurts) - Cemerlang, Anisa; , Rinasari Kusuma, M.I.Kom (2017)
Beauty is important for girls because they believe that beautiful girls can get what she wants wether career, childrens, marriage, or else that make impression beautiful girl is a must to get an easy and happy life. The meaning of beauty should be different from each individuality because it reflects on each experience, but in media shows the standard of beauty. The same standard of beauty in media make the opinion of beauty can be meassured. One of the media is music video. In Beyonce's music video, narrates about Beyonce as main actress who try hard to become the winner of beauty contest. People's assumption of beauty is something that constructed, has it owns standard which can be told that beuaty is meassured. Whereas, beauty is different from each personality from their different experiences that looked from each self concept. In this research, researcher wants to know how representation self concept of beauty in the Beyonce's music video Pretty Hurts. For answer that, research use Roland Barthes semiology analysis as an methodology through two level of meaning, denotation and connotation, with qualitative descriptive approach to know how the representation self concept of beauty presented in the Beyonce's music video Pretty Hurts. The result of this research shows four categories, there are cultural teaching, other's image, social comparison, interpretation and evaluation. Four of those categories are the source of how Beyonce value her own beauty. Interpretation is the most determine because in the last music video, Beyonce realized that her own self is enough, she's beautiful enough for her own self and she doesnt need another people tell her about her own beauty.